Global Positioning System : - Hofmann-Wellenhof, B. (Springer-Verlag, 1992)
This book is dedicated to Dr. Benjamin William Remondi for many reasons. The project of writing a Global Positioning System (GPS) book was con ceived in April 1988 at a GPS meeting in Darmstadt, Germany. Dr. Remondi discussed with me the need for an additional GPS textbook and suggested a possible joint effort.